Degradation of CCNK/CDK12 is a druggable vulnerability of colorectal cancer - Dieter, Sebastian M.; Siegl, Christine; Codó, Paula L.; Huerta, Mario; Ostermann-Parucha, Anna Lena; Schulz, Erik R.; Zowada, Martina; Martin, Sylvia; Laaber, Karin; Nowrouzi, Ali; Blatter, Mona Soledad; Kreth, Sina; et al. (Cell reports, 2021)
Novel treatment options for metastatic colorectal cancer (CRC) are urgently needed to improve patient outcome. Here, we screen a library of non-characterized small molecules against a heterogeneous collection of patient-derived CRC spheroids. By prioritizing compounds with inhibitory activity in a subset of—but not all—spheroid cultures, NCT02 is identified as a candidate with minimal risk of non-specific toxicity. Mechanistically, we show that NCT02 acts as molecular glue that induces ubiquitination of cyclin K (CCNK) and proteasomal degradation of CCNK and its complex partner CDK12. Knockout of CCNK or CDK12 decreases proliferation of CRC cells in vitro and tumor growth in vivo. Interestingly, sensitivity to pharmacological CCNK/CDK12 degradation is associated with TP53 deficiency and consensus molecular subtype 4 in vitro and in patient-derived xenografts. We thus demonstrate the efficacy of targeted CCNK/CDK12 degradation for a CRC subset, highlighting the potential of drug-induced proteolysis for difficult-to-treat types of cancer.